Symbolic Reproduction in Early Medieval England: Secular and Monastic Households. By Katharine Sykes. The Past and Present Book Series. Oxford: Oxford University Press, 2024. viii + 229 pp. $ 100.00 cloth - Brouillard, Lochin (Church history, 2025)
Symbolic Reproduction in Early Medieval England: Secular and Monastic Households. By Katharine Sykes. The Past and Present Book Series. Oxford: Oxford University Press, 2024. viii + 229 pp. $ 100.00 cloth - Volume 94 Issue 2